2013
DOI: 10.1039/c3ob41777h
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature n-butyllithium-induced [3,3]-sigmatropic rearrangement/electrophile trapping reactions of allyl-1,1-dichlorovinyl ethers. Synthesis of β-, γ- and δ-lactones

Abstract: Treatment of allyl-1,1-dichlorovinyl ethers with n-BuLi at −78°C, followed by quenching with ketones, epoxides, and oxetanes, leads to highly substituted β-, γ-, and δ-lactones in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Indeed, treatment of vinyl ether 2c with n-BuLi at −78 °C followed by methyl triflate or TMSCl (2 equiv) and then excess ethanol gave rise to α-substituted unsaturated esters in good yields, albeit with poor diastereoselectivity (Scheme 6). It was subsequently discovered that addition of symmetrical or unsymmetrical ketones to the anionic rearrangement mixture at −78 °C, followed by quench with saturated aqueous bicarbonate solution instead of alcohols, gave rise to β-lactones (20) in high overall yields. 20 Interestingly, the use of aldehydes in this reaction instead gave only low yields of the corresponding β-hydroxy acids.…”
Section: [33]-sigmatropic Rearrangement Of Allylmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, treatment of vinyl ether 2c with n-BuLi at −78 °C followed by methyl triflate or TMSCl (2 equiv) and then excess ethanol gave rise to α-substituted unsaturated esters in good yields, albeit with poor diastereoselectivity (Scheme 6). It was subsequently discovered that addition of symmetrical or unsymmetrical ketones to the anionic rearrangement mixture at −78 °C, followed by quench with saturated aqueous bicarbonate solution instead of alcohols, gave rise to β-lactones (20) in high overall yields. 20 Interestingly, the use of aldehydes in this reaction instead gave only low yields of the corresponding β-hydroxy acids.…”
Section: [33]-sigmatropic Rearrangement Of Allylmentioning
confidence: 99%
“…It was subsequently discovered that addition of symmetrical or unsymmetrical ketones to the anionic rearrangement mixture at −78 °C, followed by quench with saturated aqueous bicarbonate solution instead of alcohols, gave rise to β-lactones (20) in high overall yields. 20 Interestingly, the use of aldehydes in this reaction instead gave only low yields of the corresponding β-hydroxy acids. These results indicate the importance of the newly formed quaternary center for efficient cyclization of the presumed β-hydroxy ketene intermediate at low temperatures.…”
Section: [33]-sigmatropic Rearrangement Of Allylmentioning
confidence: 99%
“…Subsequently it was discovered that quenching the reaction with acetone in place of methanol gave rise to the corresponding rearranged β-lactones 5 (R 2 = R 3 = Me). 5 These results indicated that the species generated after [3,3]-sigmatropic rearrangement may undergo either protonation and intermolecular nucleophilic ketene trapping with alcohols or [2 + 2] cycloaddition with carbonyl compounds and protonation to provide the observed products. A likely candidate for this intermediate species is the lithium ynolate, a functional group that has been shown by Schollkopf 6 to interact with carbonyl compounds at low temperatures to provide β-lactone products in good yields.…”
mentioning
confidence: 91%
“…Thus, treatment of 1 with n -butyllithium (2.2 equiv) at −78 °C, followed by reaction quench with methanol, affords 3,4-unsaturated methyl esters 6 in good overall yields. Subsequently it was discovered that quenching the reaction with acetone in place of methanol gave rise to the corresponding rearranged β-lactones 5 (R 2 = R 3 = Me) . These results indicated that the species generated after [3,3]-sigmatropic rearrangement may undergo either protonation and intermolecular nucleophilic ketene trapping with alcohols or [2 + 2] cycloaddition with carbonyl compounds and protonation to provide the observed products.…”
mentioning
confidence: 99%
“…18 Minehan showed that the reactive intermediates obtained from n-BuLi-induced rearrangement of allyl 1,1dichlorovinyl ethers can be successfully intercepted by oxetanes to cleanly provide δ-lactones. 19 Overall, the ring-expansion reactions described above provide access to new, usefully functionalized heterocycles. In the cases where the oxetanes are readily accessible, the approaches represent efficient access to these systems.…”
mentioning
confidence: 99%